2016
DOI: 10.1007/s00038-016-0929-2
|View full text |Cite
|
Sign up to set email alerts
|

Which long-term illnesses do patients find most limiting? A census-based cross-sectional study of 340,000 people

Abstract: ObjectivesTo investigate associations between a widely used measure of self-assessed health (limiting long-term illness, LLTI) and 11 long-term health conditions.MethodsInformation on LLTI and health conditions was obtained from 2011 Census returns for a 28% representative sample of the Northern Ireland population (n = 342,868). Logistic regression was used to predict LLTI by sex and age group for each condition found in isolation, adjusting for marital status, social class, household car access, housing tenur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…This is important because there are strong trends in poor mental health prevalence with age in this population (Table 2 ) and excluding those under 40 would exclude a large proportion of those burdened with poor mental health. In this population poor mental health is most commonly found in combination with other conditions [ 48 ] and so a strength of our study was that we accounted for the presence of physical health conditions that appear to have a strong influence on mental health.…”
Section: Discussionmentioning
confidence: 99%
“…This is important because there are strong trends in poor mental health prevalence with age in this population (Table 2 ) and excluding those under 40 would exclude a large proportion of those burdened with poor mental health. In this population poor mental health is most commonly found in combination with other conditions [ 48 ] and so a strength of our study was that we accounted for the presence of physical health conditions that appear to have a strong influence on mental health.…”
Section: Discussionmentioning
confidence: 99%
“…The current study has sought to identify children based on their reported level of day-to-day impairment, and to create a measure as close as possible to the Equality Act definition. Government statistics, in contrast, tend to use measures of SEN as a proxy, which may not capture all conditions equally well (Cohen et al, 1995;Payne & Saul, 2000;Keil et al, 2006;Wright et al, 2016). In Scotland, Additional Support Needs eligibility is broad, covering all those requiring additional support due to 'learning environment, family circumstances, disability or health need, and social and emotional factors' (The Scottish Government, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation was the use of self-reported data, which in this case is more likely to have been reported by parents rather than the children themselves. As noted in the Introduction, measures of self-reported health are sensitive to various factors such as socioeconomic status and religious denomination, and may favour some health conditions more than others (Payne & Saul, 2000;O'Reilly & Rosato, 2010;Young et al, 2010;Wright et al, 2016;Black et al, 2017). Whilst this should always be borne in mind when using self-reported measures, we hope that the inclusion of a measure of specific health conditions helped to improve the accuracy of our disability measure.…”
Section: Disability and Education Outcomes 239mentioning
confidence: 94%
See 1 more Smart Citation
“…Reduced appetite resulting from a decrease in chewing and swallowing efficiency, taste and smell function, saliva production and poor oral and dental health, as well as changes in the digestive tract are associated with decreased food consumption in later life [68,69]. In addition, long-standing illnesses including diabetes, hypertension, and kidney disease requiring dietary restriction may limit food choice in older adults [70,71]. Additionally, common medications causing the reduction in appetite may contribute to inadequate intake of minerals [72].…”
Section: Coppermentioning
confidence: 99%